(untitled) (Research, Society and Development, 2020)
Isotretinoin is an important drug used for the treatment of acne, a generic name given to many skin diseases, the most common being chronic hyperactivity of the pilosebaceous follicle. Pharrmacoeconomic analysis of this drug is of paramount importance in controlling the treatment well. as in the containment of expenses by the Health System. Given the above, this paper aims to analyze the consumption of oral Isotretinoin in the specialized component of pharmaceutical care (CEAF) of the state of Piauí. To this end, a data collection was performed to survey the consumption of this drug based on the age and sex of its consumers, as well as dose, cost and dosage range. Thus, the theoretical basis focuses on articles published in the last five or ten years that will guide the interpretation of the results obtained in the field research. Thus, this study analyzed, through a statistical survey, the profile of isotretinoin consumers, demonstrating a prevalence of females as the largest consumer of the drug and highlighting the corresponding age group between 20-29 years above the statistics obtained among adolescents and adolescents most commonly used concentration of 40 mg. Information obtained from statistical data can minimize Specialized Component expenditures and contribute to treatment effectiveness.